Respectus Philologicus, 2010 Nr. 18 (23) - Bankauskaitė, Gabija (Respectus Philologicus, 2010)
CONTENTS I. PROBLEMS AND SOLUTIONS Isabel Íñigo-Mora, Gloria Álvarez-Benito (Spain). Gestures and Words in Political Discourse: a Case Study of the Obama-McCain Encounter... 11 Vadim V. Dementyev (Russia). Anecdote in the Era of Censorship: Types of Public Representation (Experience of Diachronic Analysis of Anecdots on the Material of the Magazine Krokodil)... 26 Daiva Aliūkaitė (Lithuania). New Dialect: the Possible Scenario of Dialectal Discourse Estimation...41 Marek Ruszkowski (Poland). Krylov Law in Polish Linguistic Research...58 II. FACTS AND REFLECTIONS Loreta Ulvydienė (Lithuania). Literature after 9/11: John Updike’s Terrorist...64 Fryderyk Listwan (Poland). Comment on Intertextuality: Allusion in Leonid Leonov’s Publicistic Writings... 74 Inesa Šeškauskienė (Lithuania). Who Discusses: the Paper or the Author of the Paper? Inanimate Subject + Active Verb in Lithuanian Linguistic Discourse as Compared to English...83 Eleonora Lassan (Lithuania). On some Phenomena of Modern Russian Rhetoric in Public Communication (Rhetoric of Nostalgia as a Result of a Dialogue with the Past)...100 Maria А. Sivenkova (Belarus). ‘Again, a Stupid Question!’ or How Politicians Criticise the Questions they are Being Asked...111 Gayane R. Vlasyan (Russia). Communicative-Pragmatic Peculiarities of Counter-Questions in English Dialogical Discourse...126 Jolanta Vitkauskienė (Lithuania). A Way of Analyzing Perlocutionary Speech Acts...135 Gabija Bankauskaitė-Sereikienė, Justina Vaitelytė (Lithuania). Cultural Values in the Advertisements of New Romuva (1931–1940)...145 Lina Inčiuraitė (Lithuania). Conceptual Metaphors of Sawel in Ælfric’s Catholic Homilies...159 Liudmila Arcimavičienė (Lithuania). Cognitive Approach to language teaching. Cultural reality through Metaphor: a Case Study of Birthday Wishes...170 Liudmila Garbul (Lithuania). Reflection of Results of Interslavonic Language Contacts in the Russian Chancery Language of the First Half of the 17th Century (Synchronic and Diachronic Aspects)...179 Audronė Gedžiūtė, Jadvyga Krūminienė (Lithuania). A Semiotic Attempt at the Reconstruction of Celtic Mythical Models: the Figure of the Horse...191 Danguolė Melnikienė (Lithuania). Are Onomatopoeic Interjections Necessary in a Bilingual Dictionary?...202 Laura Kamandulytė-Merfeldienė (Lithuania). The Usage of Colour Terms in the Early Childhood...212 Nijolė Tuomienė (Lithuania). Southern Aukštaitian Dialect in Belarus: the Result of Language Interplay...223 Rima Bacevičiūtė (Lithuania). Features of Žemaitian Dialect of the Lithuanian Language in the Western Aukštaitian Subdialect of Kaunas...235 Lidija Kaukėnienė (Lithuania). The Duration of Long Vowels in Standard Latvian...244 III. OPINION Oleg Leschak (Poland). Methodological Character of Scientific Translation (Footnotes of Ferdinande de Saussure’s De l’essence double du langage. Translation into the Polish Language)... 252 IV. OUR TRANSLATIONS Bernard Sypniewski (USA). Snake in the Grass. Part I. Translated by Jurga Cibulskienė...265 V. SCIENTIFIC LIFE CHRONICLE Books reviews Leonid P. Krysin (Russia). LUCIŃSKI, Kazimierz, 2009. Языковые заимствования и ментальность...273 Dagnė Beržaitė (Lithuania). On English Dostoevsky in Lithuanian. MORRIS, R. N., 2009. Švelnus kirvis. MORRIS, R. N., 2009. Kerštingas potroškis...274 Viktorija Makarova (Lithuania). On the most Important of all Arts. ARLAUSKAITĖ, Natalija, 2010. Trumpas feministinės kino teorijos žinynas... 278 Vilnius University Kaunas Faculty of Humanities: journal of scientific life Giedrė Lankutytė (Lithuania). Advertisement Creators Accept START! Challenge...279 In Memoriam Умер Аркадий Бартов... 282 Arkady Bartov dies... 283 Announce...284 VI. REQUIREMENTS FOR PUBLICATION...285 VII. OUR AUTHORS...293